Does adjusting for health-related quality of life matter in economic evaluations of cancer-related interventions?. (February 2011) - Greenberg, Dan; Neumann, Peter J
Aims: We investigated the extent to which adjusting for health-related quality of life (HRQoL) alters incremental cost per life-year gained ratios, and the implications for reimbursement decisions.Methods: We identified all cancer-related interventions in the Tufts Medical Center Cost––Effectiveness Analysis Registry in which both a cost/quality-adjusted life-year (QALY) and a cost/life-year ratio were reported in the same study. We assessed the ordinal relationship between these ratios and analyzed the extent to which using a cost/QALY rather than a cost/life-year ratio would potentially yield different reimbursement decisions.Results: The rank––order correlation between cost/life-year and cost/QALY ratio pairs was 0.917 (p < 0.0001). In 78.8% of comparisons, both cost/QALY and cost/life-year ratios were below a prespecified threshold (e.g., US50, 000 per QALY or life-year). Adjusting for HRQoL resulted in a higher ratio such that it crossed a prespecified threshold in 18.6% of interventions. The data suggest that adjusting life-years for HRQoL does not substantively affect cost per life-year ratios for the vast majority of cancer-related interventions.Conclusion: Our analysis implies that the method used for HRQoL adjusting or even HRQoL adjusting at all does not matter for most reimbursement decisions on life-saving interventions. The results could differ for interventions that have large impacts on patients'' HRQoL compared with the impact on survival.